1995
DOI: 10.1046/j.1469-0705.1995.06030182.x
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic incidence of polycystic ovaries in a gynecological population

Abstract: The prevalence of polycystic ovaries in a large population of 1078 women of reproductive age was determined by pelvic ultrasonography. The ovarian ultrasonic appearance of 183 (17%) women met the morphological criteria of polycystic ovaries. Of these women, 147 (80.3%) had irregular cycles (group A) and 36 (19.7%) had normal cycles (group B). The remaining women constituted the control group. Ovarian volume was calculated in all women in whom at least one ovary was visualized. Serum levels of luteinizing hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 0 publications
2
25
3
Order By: Relevance
“…This prevalence of polycystic ovaries (41%) in the women with previous GDM is twice as large as that reported for premenopausal women overall (16,17,32). The figure should be regarded as approximate and in need of verification by further studies because dropouts may introduce some selection bias.…”
Section: Discussionmentioning
confidence: 67%
“…This prevalence of polycystic ovaries (41%) in the women with previous GDM is twice as large as that reported for premenopausal women overall (16,17,32). The figure should be regarded as approximate and in need of verification by further studies because dropouts may introduce some selection bias.…”
Section: Discussionmentioning
confidence: 67%
“…PCO have been found in childhood, the prevalence increasing with age from 6% at 6 years of age, until 26% of the scans at 15 years of age (Bridges et al, 1993). The prevalence of PCO in normal women of reproductive age is reported to range from 14% to 33% (Polson et al, 1988;Clayton et al, 1992;Botsis et al, 1995;Michelmore et al, 1999;Koivunen et al, 1999). Taponen et al (2004) found 47.9% of women with oligomenorrhoea only, 18.4% hirsutism only and 70.4% with both symptoms to have PCO.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have resulted in estimates of prevalence, in women of reproductive age, that range from 6.5% to 8% using biochemical and/or clinical evidence, [4][5][6][7] and ultrasound-based studies have reported a prevalence of 20% or more. [8][9][10][11] Therefore, in a population of seven million Canadian women aged between 15 and 44 years, as many as 1.4 million women may be afflicted with this disorder. 12 It has been our experience that many, if not most, women are first given a diagnosis of PCOS when they present to a reproductive endocrinologist with infertility, and that in the years following last delivery and continuing to reproductive senescence there is a clear tendency to forgo long-term management of symptoms.…”
Section: Introductionmentioning
confidence: 99%